Մերձավոր և Միջին Արևելքի երկրներ և Ժողովուրդներ, XVIII - Խմբ.` Ն. Հովհաննիսյան («Զանգակ - 97»)
Many aspect of the Yezidism, one of the most esoteric and interesting confessions, until present days need additional and more deep investigation. One of them, of course, is the problem of partial taboo on the blue color.
Keywords: Պատմություն; Մերձավոր Արևելք; Միջին Արևելք